(untitled) (Andamios, Revista de Investigación Social, 2025)
This article studies the different ways in which discrimination processes play out in the everyday social interactions of the blind people and how these are perceived and challenged. To do so, I propose a renewed reading of Erving Goffman’s (1963) notion of stigma, basing my analysis upon ethnographic fieldwork among people with visual disabilities in the city of Cuenca, Ecuador, conducted between 2013 and 2020. In exploring the ways that stigma is expressed, and how the responses to it are constructed, we found it manifested in five ways: fear and masking on the part of blind people; and simplification, indifference, and pity on the side of their interlocutors. I argue that this typology operates in an integrated way and that its effects in the lives of the blind people are detrimental. It contributes to the construction of stereotypes, it diminishes their expectations and possibilities for individual fulfillment and reinforces their isolation and exclusion; and at the same time it gives people agency and an opportunity for social vindication.